1982
DOI: 10.1677/joe.0.0940083
|View full text |Cite
|
Sign up to set email alerts
|

Role of serotoninergic neurones in the control of gonadotrophin and prolactin secretion in the rat

Abstract: The role of brain serotonin (5-hydroxytryptamine, 5-HT) in the control of LH, FSH and prolactin secretion was studied in two groups of experimental animals: intact adult male rats and ovariectomized adult female rats. 5-Hydroxytryptophan (5-HTP), a precursor of serotonin synthesis, and fluoxetine, a specific inhibitor of 5-HT uptake, were given either alone or together. 5\ x =r eq-\ Hydroxytryptophan (50 mg/kg) was administered intraperitoneally and fluoxetine (20 \g=m\g/rat) was given into one of the lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…A double dose was unable to potentiate the PRL secretion suggesting that the dose employed in this study, commonly used in clinical practice, is already at the maximal action level. A similar serotoninergic stimulatory effect on rat PRL secretion has been previously reported [14,15,40,41].…”
Section: Discussionsupporting
confidence: 85%
“…A double dose was unable to potentiate the PRL secretion suggesting that the dose employed in this study, commonly used in clinical practice, is already at the maximal action level. A similar serotoninergic stimulatory effect on rat PRL secretion has been previously reported [14,15,40,41].…”
Section: Discussionsupporting
confidence: 85%
“…In prepubertal rats, serotonin is capable of stimulating LH and FSH [8], whereas in adult rats the findings are more confusing [7]. But several investigators reported increased LH secretion in rats and ewes due to serotoninergic stimulation [9, 10, 11]. Stimulation of LH secretion is the result of direct action at the pituitary level [11] as well as increased GnRH release from the median eminence [12].…”
Section: Discussionmentioning
confidence: 99%
“…In ovariectomized rats, activation of central serotonin activity led to an increased LH secretion [9]. Contrary results have also been reported [19, 20] depending on the route of drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of 5-HT as intra ventricular [Kamberi et al, 1971] or systemic injection [Lawson and Gala, 1978], or the administration of precursors [Lu and Meites, 1973;Chen and Meites, 1975;Ruzsas et al, 1982] or receptor agonists [Lawson and Gala, 1978;Krulich et al, 1979] increased plasma prolactin levels. Furthermore serotonin up take antagonists potentiate the releasing ef fect of 5-HT precursors [Krulich.…”
mentioning
confidence: 99%
“…Some data suggest that 5-HT stimu lates LH secretion [Wuttke et al, 1977;Van de Kar et al, 1980;Chen et al, 1981;Ruzsas et al, 1982] whereas others show the oppo site [Kamberi et al, 1970;Ladosky and Noronha, 1974;Pilotte and Porter, 1979], From the few available data regarding the effects of serotonin on FSH secretion, both an inhibi tory action and no effect have been described [Kamberi et al, 1971;Wuttke et al, 1977;Ruzsas et al, 1982], It has been generally agreed that rats neonatally injected with sex steroids show changes in gonadotropins and prolactin se cretion in adulthood [Mallampatli andJonson, 1973a, b, 1974;Mogiulevski et al, 1978;Aguilar et al, 1984] together with modifica tions in their aminergic systems [Vaccari. 1980;Demurest et al, 1981;Lookingland et al, 1982],…”
mentioning
confidence: 99%